Spread associations of hoof pathology in donkeys in the central and eastern regions of Ukraine - B. Kyrychko; O. Sakharova (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2022)
Interest in keeping a donkey as a working, productive, sports and entertainment, and companion animal is constantly growing both in the countries of the world and in Ukraine. However, unlike other countries, in Ukraine, sufficient attention should have been paid to hoof diseases in donkeys for an extended period. Having studied foreign research on this problem and having conducted our research on the spread of donkey hoof pathologies in the central and eastern regions of Ukraine, we concluded that this problem requires in-depth research since hoof pathologies are primarily associated. The hoof has many anatomical components that are closely related to each other and must function in harmony. Therefore, the occurrence of a disease in one anatomical component entails pathological conditions in others. We have conducted a systematization of the data obtained during the study of the distribution of hoof pathologies in donkeys in the central and eastern regions of Ukraine, and we have discovered 59 associations of hoof pathologies with different compositions. 90 % of the donkeys in the experiment had from 2 to 9 hoof pathologies simultaneously, and there were no donkeys with a single separate hoof disease among the examined animals. It was also established that 80.6 % of examined donkeys had from 5 to 8 hoof pathologies simultaneously. Most often, associations of hoof pathologies consisted of 8 different diseases (24.3 %). Associations with two and three-hoof pathologies (2.1 and 4.2 %) were the least common. We also investigated the qualitative composition of associations of hoof pathologies in donkeys and revealed a certain regularity and dependence of the formation of hoof pathologies in donkeys. Moreover, the widest qualitative variety of hoof pathologies had 13 different associations consisting of precisely five pathologies. During our study of the mechanisms of formation of associations of hoof pathologies, we noted that overgrown hooves, various forms of hoof imbalance, and hoof onychomycosis (surface impression of the hoof horn by keratophages of fungal and bacterial origin) are among the main starting pathologies of hooves in donkeys. In advanced cases, severe pathologies of the hooves occurred, such as contracture of the superficial digital flexor, hypoplasia of the flexors, or deformation of the hoof wall. These pathologies caused inflammatory and destructive processes in various structures of the hoof, which in association led to a partial or complete loss of work capacity and productivity of donkeys and deterioration of their well-being and health.